Bearing Capacity Modification Of Clay In The Kedungsigit Village Using Zeolite - Krisdiyanto Nugroho; Agata Iwan Candra; Yosef Cahyo Setianto Poernomo (Kadiri University, 2021)
Clay is a type of soil with a high level of water content. These properties make clay soils have a low low bearing capacity which can have an impact on the buildings above them, such as cracked walls, raised foundations, bumpy roads and so on. The soil in Kedungsigit Village, Karangan District, Trenggalek Regency is clay and needs to be repaired to build a strong building. This study aims to modify the value of the bearing capacity of clay. Modifications were made by adding Zeolite with a percentage of 0%, 5%, 10%, 15%, and 20%. Zeolite is used because it contains mineral kristal alumina silikat which have the ability to bind grains between aggregates. Observations were made on the characteristics of clay including testing of volume weight, shear strength, and bearing capacity using the Terzaghi method. The results showed the optimum value for the addition of 15. In testing the bearing capacity of the soil using the tread foundation, the value of 32,470 t/m2 was obtained for the addition of 15% zeolite and 21,376 t/m2 for the original soil. From these results it is known that the use of zeolite can increase the value of the bearing capacity of the soil. So that these modifications can be used as an effort to improve soil in Kedungsigit village.